Perencanaan Sistem Database Penempatan Tenaga Kerja Berbasis Web dengan Pendekatan Work Breakdown Structure dan COCOMO - Aris Martono (Rekayasa Teknologi, 2012)
The project plan of manpower replacement system based on web is to aim preparing the system, supported tools and kinds of informations that be inputed in database oninternet so that some stakeholders—job seeker, company, higher education (to supplyexperts)and government as facilitator—can access the database system accurately,relevant and on-time.The project plan system had been done in Department of Manpower and Transmigrationthat be used of guidance for measuring the system project modul with work breakdownstructure dan constructive cost model (Cocomo) so it is easy to make a project costproposal.The result of calculation of the both approaches are the time schedule needs 7.68months where the product design modul needs 1.23 months with experts are 2.49 manmonths,the detaileddesignmodulneeds1.86monthswith expertsare2.5man-months,thecode modul and unit test need 2.51 months with experts are1.64 man-months.The project plans can be concluded as follows : (1) can be known the results ofestimated calculation for experts and time each activity; (2) can be made the organizationchart included experts and their tasks; and (3) can be made the time schedule.